The aristotelisation and platonisation of Parmenides by Simplicius - Cordero, Néstor Luis (AADEC - UNL, 2015)
The difficulty in understanding Parmenides’ thought has led the interpreters, from Antiquity onwards, to study his philosophy according to later schemes of thought. It was the case of Aristotle, whose interpretation will be inherited by his disciple Theophrastus and his commentators, specially Simplicius. Simplicius, Neoplatonic and Aristotelian at the same time, proposed an interpretation strongly dualistic (dominated by the alternative intelligible/sensible) that we cannot find in the literal quotations that have been recuperated. It was in 1789 that G.G.Fülleborn, inspired on Simplicius, proposed a division of the Poem in two “parts”, division accepted unanimously today. This division should be urgently reviewed and rejected.